Analysis of clinical characteristics and treatment of immunoglobulin G4-associated cholangitis: A retrospective cohort study of 39 IAC patients. Issue 8 (February 2018) - Xiao, Jianchun; Xu, Peiran; Li, Binglu; Hong, Tao; Liu, Wei; He, Xiaodong; Zheng, Chaoji; Zhao, Yupei
Abstract : Abstract: Immunoglobulin (Ig)G4-associated cholangitis (IAC) is one of the common organ manifestations of IgG4-related systemic disease (ISD). IAC and autoimmune pancreatitis (AIP) may mimic sclerosing cholangitis, cholangiocarcinoma, or pancreatic carcinoma. Diagnosis is based on a combination of clinical, biochemical, radiological, and histological findings. To study the clinical presentation of and treatment strategy for IAC, we reviewed clinical, serologic, and imaging characteristics, as well as treatment response, in 39 patients with IAC. The majority of patients were men (82%). Clinical features on presentation included obstructive jaundice in 26 patients (67%) and abdominal pain in 20 (51%). Positive IgG4 immunostaining was seen in 27 patients. The median serum IgG4 level before treatment was 769.4 mg/dL (range, 309.1–1229.7 mg/dL). After the steroid therapy, the median serum IgG4 level in 23 patients was 247.0 mg/dL (range, 139.0–355.0 mg/dL). Cholangiograms were available in 36 (92%) patients. Stenosis of the lower part of the common bile duct was found in 26 of 39 patients. Stenosis was diffusely distributed in the intra- and extrahepatic bile ducts in 14 of 39 patients. Additionally, strictures of the bile duct were detected in the hilar hepatic lesions in 27 of 39 patients. AIP was the most frequent comorbidity (35/39 in this study) of IAC. Other affected organs included eyes (n = 6), salivary glands (sialadenitis, n = 10), lymph nodes (mediastinal and axillary, n = 3), kidneys (n = 2), and the retroperitoneum (retroperitoneal fibrosis, n = 2). Regarding treatment, 29 patients were treated with steroids, of whom one underwent pancreatoduodenectomy, and one underwent choledochojejunostomy. Eight patients were treated with biliary stents. The remaining 19 patients took prednisolone alone. Eight patients achieved spontaneous resolution. Four patients with suspected pancreatic cancer or cholangiocarcinoma underwent surgery, including 2 patients who also received postoperative steroids. All patients were regularly followed up for 9 to 36 months. Only 2 patients in the steroids treatment group relapsed to manifest obstructive jaundice and high serum IgG4 levels. These 2 patients were treated with steroids and biliary stents, resulting in complete remission. We also review the diagnostic and therapeutic management and discuss recent pathophysiological findings, which might aid in understanding the molecular mechanisms contributing to IAC and other manifestations of IgG4-related diseases (IgG4-RD). Biomarkers that are more accurate are needed to correctly diagnose IAC and prevent misdiagnoses and unnecessary therapeutic interventions.